Creating a Sustainable Entrepreneurship Ecosystem Through Innovation in Education - Herlina, Herlina; Wahira, Wahira (International Journal of Engineering, Science and Information Technology, 2024)
People increasingly recognize entrepreneurship as a critical strategy for driving economic growth, reducing unemployment, and fostering innovation across sectors. However, entrepreneurship's sustainability relies heavily on supporting a robust ecosystem, with education serving as its foundation. Innovations in education, such as project-based learning (PBL), business simulations, and collaborations between educational institutions, industry, and government, are essential for shaping resilient, innovative, and sustainable entrepreneurs. Research has demonstrated that ecosystem-based entrepreneurship education enhances critical thinking skills, creativity, adaptability, and entrepreneurial readiness to tackle global challenges. Multi-stakeholder collaborations between education, industry, and government strengthen this ecosystem by providing resources, networks, and knowledge that support business sustainability. Additionally, challenge-based learning approaches such as Challenge-Based Learning (CBL) and the integration of business simulations effectively increase entrepreneurial confidence and learning performance through real-world experiences. This strategy has the potential to significantly and sustainably influence economic development through the ecosystem of entrepreneurship education. This study takes a qualitative approach, analyzing books, policy papers, case studies, and scientific articles on entrepreneurship education from different higher education institutions using a literature review method. We perform the analysis using a descriptive methodology to find trends, themes, and successful tactics in entrepreneurship education. Building a healthy entrepreneurial ecosystem requires innovation in entrepreneurship education. Approaches such as project-based learning and business simulations provide students with relevant practical experiences, helping them develop skills such as decision-making, risk management, and innovation needed to navigate the dynamics of modern business. Furthermore, collaboration between the education sector, industry, and government is critical in creating an ecosystem that supports innovative and resilient entrepreneurs. Studies show that innovation-based education, supported by multi-stakeholder collaboration, improves students' readiness for business challenges and contributes to sustainable economic and social growth.